The Use of Interferon Gamma Inducible Protein 10 as a Potential Biomarker in the Diagnosis of Latent Tuberculosis Infection in Uganda - Biraro, Irene Andia; Kimuda, Simon; Egesa, Moses; Cose, Stephen; Webb, Emily L.; Joloba, Moses; Smith, Steven G.; Elliott, Alison M.; Dockrell, Hazel M.; Katamba, Achilles (PLoS ONE, 2016)
In the absence of a gold standard for the diagnosis of latent tuberculosis (TB) infection (LTBI), the current tests available for the diagnosis of LTBI are limited by their inability to differentiate between LTBI and active TB disease. We investigated IP-10 as a potential biomarker for LTBI among household contacts exposed to sputum positive active TB cases. Methods Active TB cases and contacts were recruited into a cohort with six months’ follow-up. Contacts were tested for LTBI using QuantiFERON1-TB Gold In-Tube (QFN) assay and the tuberculin skin test (TST). Baseline supernatants from the QFN assay of 237 contacts and 102 active TB cases were analysed for Mycobacterium tuberculosis (MTB) specific and mitogen specific IP-10 responses. Results Contacts with LTBI (QFN+TST+) had the highest MTB specific IP-10 responses at baseline, compared to uninfected contacts (QFN-TST-) p<0.0001; and active cases, p = 0.01. Using a cut-off of 8,239 pg/ml, MTB specific IP-10 was able to diagnose LTBI with a sensitivity of 87.1% (95% CI, 76.2–94.3) and specificity of 90.9%(95% CI, 81.3–96.6). MTB specific to mitogen specific IP-10 ratio was higher in HIV negative active TB cases, compared to HIV negative latently infected contacts, p = 0.0004. Concentrations of MTB specific IP-10 were higher in contacts with TST conversion (negative at baseline, positive at 6-months) than in those that were persistently TST negative, p = 0.001. Conclusion IP-10 performed well in differentiating contacts with either latent or active TB from those who were uninfected but was not able to differentiate LTBI from active disease except when MTB specific to mitogen specific ratios were used in HIV negative adults. In addition, IP-10 had the potential to diagnose ‘recent TB infection’ in persons classified as having LTBI using the TST. Such individuals with strong IP-10 responses would likely benefit from chemoprophylaxis.
Keywords: Gamma Inducible Protein; Potential Biomarker; Latent Tuberculosis Infection